Effect of Different Aggregate Gradation on the Properties of Pervious Concrete - Prakash, Pravin; Daniyal, Mohammed (AMC Indian Journal of Civil Engineering, 2025)
This study investigates the influence of aggregate gradation on the physical, mechanical, and hydrological properties of pervious concrete. Five mix designs with varying proportions of 10 mm, 12.5 mm, and 20 mm coarse aggregates were evaluated to understand their effects on unit weight, compressive strength, porosity, workability, and permeability. Results demonstrated strong correlations: higher unit weight corresponded to increased compressive strength due to improved particle packing and reduced voids, while porosity showed an inverse relationship with strength, highlighting the impact of internal void content on structural performance. Workability, measured by spread diameter, was found to slightly affect permeability, as better paste distribution reduced pore connectivity and flow rates. Among all mixes, the well-graded Mix D (40% 10 mm, 30% 12.5 mm, 30% 20 mm) achieved the best balance, exhibiting the highest compressive strength, lowest porosity, and moderate permeability suitable for pervious concrete applications requiring both durability and effective drainage. These findings underscore the critical role of aggregate gradation in optimizing pervious concrete performance for diverse engineering needs.